Antimicrobial Assay of Soil Mold Isolates from Wonorejo Surabaya - Arisanti, Septia; Kuswytasari, Nengah Dwianita; Shovitri, Maya (IPTEK The Journal for Technology and Science, 2012)
This study was aimed to an examine antimicrobial activity of 34 soil molds isolates from the Wonorejo Surabaya on the growth of Gram negatif bacteria (Escherichia coli and Coliform Bacteria Group), Gram positif bacteria (Bacillus subtilis) and yeast (Saccharomyces cerevisiae). Antimicrobial ability detected with modification of dual culture antagonism assay in Potato Dextrose Agar (PDA) medium. The result showed that genus Aspergillus, Scopulariopsis, Penicillium, Paecilomyces, Fusarium, and Trichoderma were able to inhibit E. coli; while genus Aspergillus, Scopulariopsis, Penicillium, Paecilomyces, Exophiala, Stachybotrys, and Acremonium inhibit B. subtilis; further on only genus Aspergillus could inhibit group of Coliform bacteria); and genus Scopulariopsis, Penicillium, Trichoderma, and Absidia inhibited the growth of yeast S. cerevisiae.